Traditional Knowledge to Contemporary Medication in the Treatment of Infectious Disease Dengue: A Review - Dhiman, Mamta; Sharma, Lakshika; Dadhich, Abhishek; Dhawan, Poonam; Sharma, M. M. (Frontiers in Pharmacology, 2022)
Dengue has become a worldwide affliction despite incessant efforts to search for a cure for this long-lived disease. Optimistic consequences for dengue vaccine are implausible as the efficiency is tied to previous dengue virus (DENV) exposure and a very high cost is required for large-scale production of vaccine. Medicinal plants are idyllic substitutes to fight DENV infection since they constitute important components of traditional medicine and show antiviral properties. Though, the mechanism behind the action of bioactive compounds to obstruct viral replication is less explored and yet to be discovered. This review includes the existing traditional knowledge on how DENV infects & multiplies in the host cells, conscripting different medicinal plants obtained bioactive compounds with anti-dengue properties, and the probable mechanism on how bioactive compounds modulate the host immune system during DENV infection. Moreover, different plant species having such bioactive compounds reported for anti-DENV efficiency should be validated scientifically via different In vitro & In vivo studies.